WORD FORMATION PROCESS IN NOVEL ALICE’S ADVENTURES IN WONDERLAND BY LEWIS CARROLL AND MOVIE ALICE IN WONDERLAND BY WALT DISNEY - Sonia Rizki; Leni Marlina (Universitas Negeri Padang, 2018)
Word-formation is the study of words, dealing with the construction or formation rules of words in a certain language. This research paper is aimed to investigate word formation process used in “Alice’s Adventures in Wonderland” novel by Lewis Carroll and “Alice in Wonderland” movie by Walt Disney. This research paper uses O’Grady (1997) and Yule (2010) theories about word formation process. This study used qualitative approach with descriptive method. The writer found affixation as the dominant type used to form the words in the novel that occurred in 286 data or about 48,89%, and 15 data or about 30,61% cliticization as the dominant type to form the words in the movie script.